Review of “Post-industrial development in east Asia, Taiwan and South Korea in comparison” by Min-hua Chiang, Palgrave Macmillan, 2018 - Kamaruddin, Nurliana (AEI Insights, 2021)
There has been no shortage of books discussing the impressive economic development experience of East Asian countries in the past few decades. Thirty years since the publication of Chalmers Johnson’s seminal work “MITI and the Japanese Miracle: The Growth of Industrial Policy 1925-1975”, scholars have continued to examine and debate the circumstances that define and shape the economic success of East Asian countries. Today, much of the interest lies with China’s growth and dominance, however, South Korea’s and Taiwan’s development are also significant as they are the only other two non-city state countries that have achieved rapid economic growth since the end of the Second World War. For Malaysia, the recent change in government has brought about a re-emergence of the Look East Policy and renewed interest in learning from the countries in East Asia. Min-Hua Chiang’s book “Post-Industrial Development in East Asia, Taiwan and South Korea in Comparison” provides a detailed insight in the recent development progress of South Korea and Taiwan since the mid-1990s to the present. As South Korea and Taiwan are also major trading partners for Malaysia, the development experience of these countries can provide significant lessons that would benefit local policy makers and scholars alike.